2005
DOI: 10.1590/s1415-47572005000400013
|View full text |Cite
|
Sign up to set email alerts
|

In silico characterization of microsatellites in Eucalyptus spp.: abundance, length variation and transposon associations

Abstract: This study assessed the abundance of microsatellites, or simple sequence repeats (SSR), in 19 Eucalyptus EST libraries from FORESTs, containing cDNA sequences from five species: E. grandis, E. globulus, E. saligna, E. urophylla and E. camaldulensis. Overall, a total of 11,534 SSRs and 8,447 SSR-containing sequences (25.5% of total ESTs) were identified, with an average of 1 SSR/2.5 kb when considering all motifs and 1 SSR/3.1 kb when mononucleotides were not included. Dimeric repeats were the most abundant (41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
(29 reference statements)
6
16
1
Order By: Relevance
“…For example, (GT)n was found to be the most frequent repeat in mammals, whereas in plants and vertebrates, the dominant repeats were (AT)n and (CT)n, respectively (Lagercrantz et al, 1993;Paxton et al, 1996). Our results revealed that mononucleotide repeats were the most frequent SSRs in the F. vesca genome (such as A/T, representing 52.92% of total SSRs), followed by dinucleotide repeats (AT/TA, 14.43%), which is in stark contrast to results from previous studies (Cardle et al, 2000;Varshney et al, 2002;Rabello et al, 2005). This notable difference with previous results might be due to the fact that previous genome information was not complete, or that molecular hybridizations were the only methods previously available.…”
Section: Relationship Between Ssr Abundance and Genome Sizecontrasting
confidence: 99%
See 2 more Smart Citations
“…For example, (GT)n was found to be the most frequent repeat in mammals, whereas in plants and vertebrates, the dominant repeats were (AT)n and (CT)n, respectively (Lagercrantz et al, 1993;Paxton et al, 1996). Our results revealed that mononucleotide repeats were the most frequent SSRs in the F. vesca genome (such as A/T, representing 52.92% of total SSRs), followed by dinucleotide repeats (AT/TA, 14.43%), which is in stark contrast to results from previous studies (Cardle et al, 2000;Varshney et al, 2002;Rabello et al, 2005). This notable difference with previous results might be due to the fact that previous genome information was not complete, or that molecular hybridizations were the only methods previously available.…”
Section: Relationship Between Ssr Abundance and Genome Sizecontrasting
confidence: 99%
“…Here, 2 different patterns were observed with respect to the general relationship between the proportion of SSR lengths and the number of repeated units. First, there were well-defined decay curves when moving from trinucleotide to hexanucleotide repeats, and second, this trend was not observed in either mononucleotide or dinucleotide repeats, which is in concordance with the results of Varshney et al (2002) and Rabello et al (2005).…”
Section: Relationship Between Evolution and Repeated Unit Lengthsupporting
confidence: 90%
See 1 more Smart Citation
“…This is an agreement with genomic DNA analysis of Arabidopsis (Lawson and Zhang 2006), where A/T motifs were abundant among the monomer repeats in EST libraries. Similar results were also seen in eucalyptus (Rabello et al 2005) and in many other crop species (Gao et al 2003). In mycobacterial genomes stretches of long monomer repeats were noticed as they act as contingency loci (Sreenu et al 2007).…”
Section: Type Of Ssrs and Motif Groups In Cacao Ests And Contigssupporting
confidence: 75%
“…The estimated frequency of SSRs in cacao ESTs was one per 26.9 kb, based on the total size of the examined sequences (2616452 bp). The frequency of SSRs in ESTs of other crops reported earlier were one per 11.8 kb in rice; one per 23.8 kb in soybean, one per 17.24 kb in wheat and one per 28.32 kb in maize (Gao et al 2003) and one per 2.5 kb in eucalyptus (Rabello et al 2005). But the SSR frequency can follow a unique pattern in a plant species where seven-fold variation was seen in 24 plants of widely differing taxa with a mean of 114.7 SSRs per Mb (von Stackelberg et al 2006) with a standard deviation of +/− one per 60.1 Mb.…”
Section: Frequency Of Ssrs In Cacao Ests and Contigsmentioning
confidence: 80%